PTEN Directly Activates the Actin Depolymerization Factor Cofilin-1 During PGE(2)-Mediated Inhibition of Phagocytosis of Fungi - Serezani, C. Henrique; Kane, Steve; Medeiros, Alexandra Ivo de [UNESP]; Cornett, Ashley M.; Kim, Sang-Hoon; Marques, Mariana Morato; Lee, Sang-Pyo; Lewis, Casey; Bourdonnay, Emilie; Ballinger, Megan N.; White, Eric S.; Peters-Golden, Marc (Amer Assoc Advancement Science, 2012)
Macrophage ingestion of the yeast Candida albicans requires its recognition by multiple receptors and the activation of diverse signaling programs. Synthesis of the lipid mediator prostaglandin E-2 (PGE(2)) and generation of cyclic adenosine monophosphate (cAMP) also accompany this process. Here, we characterized the mechanisms underlying PGE(2)-mediated inhibition of phagocytosis and filamentous actin (F-actin) polymerization in response to ingestion of C. albicans by alveolar macrophages. PGE(2) suppressed phagocytosis and F-actin formation through the PGE(2) receptors EP2 and EP4, cAMP, and activation of types I and II protein kinase A. Dephosphorylation and activation of the actin depolymerizing factor cofilin-1 were necessary for these inhibitory effects of PGE(2). PGE(2)-dependent activation of cofilin-1 was mediated by the protein phosphatase activity of PTEN (phosphatase and tensin homolog deleted on chromosome 10), with which it directly associated. Because enhanced production of PGE(2) accompanies many immunosuppressed states, the PTEN-dependent pathway described here may contribute to impaired antifungal defenses.